Impact of the ceramide subspecies on the nanostructure of stratum corneum lipids using neutron scattering and molecular dynamics simulations. Part I: impact of CER[NS]. (August 2018) - Schmitt, Thomas; Gupta, Rakesh; Lange, Stefan; Sonnenberger, Stefan; Dobner, Bodo; Hauß, Thomas; Rai, Beena; Neubert, Reinhard H.H.
Graphical abstract: Highlights: Neutron diffraction and molecular simulations on CER[NS]/[AP] stratum corneum models, show minute details of the lamellar nanostructure. Overlapping of the long C24 chain in the lamellar middle demonstrates unique and biophysically relevant properties. Differences between [NS] and [NP] can be shown: Miscibility, lateral/perpendicular order, chain tilt/opening. Simulated bilayers and triple layers show distinct structural differences. An indication of a possible cholesterol flip-flop mechanism is shown. Abstract: For this study mixtures based on the ceramides [NS] (NS = non-hydroxy-sphingosine) and [AP] (AP = α-hydroxy-phytosphingosine) in a 2:1 and 1:2 ratio, together with cholesterol and lignoceric acid, were investigated. These mixtures are modelling the uppermost skin layer, the stratum corneum . Neutron diffraction, utilizing specifically deuterated ceramide molecules, was used to obtain a maximum amount of experimental detail. Highly detailed molecular dynamics simulations were used to generate even more information from the experimental data. It was possible to observe a single lamellar phase for both systems. They had a lamellar repeat distance of 5.43 ± 0.05 nm for the [NS]/[AP] 2:1 and a slightly shorter one of 5.34 ± 0.05 nm for the 1:2 system. The structure and water content was uninfluenced by excess humidity. Both the experimental and simulation data indicated slightly tilted ceramides, with their C24 chains overlapping in the lamellar mid-plane. This arrangement is well comparable to systems investigated before. The structure of both systems, except for the differing repeat distance, looks similar at first. However, on a smaller scale there were various distinct differences, demonstrating only low redundancy between the different ceramide species, despite only minor chemical differences. The mainly ceramide [AP] determined 1:2 system has a slightly smaller repeat distance. This is a result of a tighter arrangement of the lipids chain along the bilayer normal and increased overlapping of the long chains in the lamellar middle. For the CER[NS] some novel features could be shown, despite it being the overall most investigated ceramide. These include the low adaptability to changed lateral interactions, leading to an increased chain opening. This effect could explain its low miscibility with other lipids. The investigated model systems allows it to directly compare results from the literature which have used ceramide [NS] to the most recent studies using the phytosphingosine ceramides such as ceramide [AP].